2015
DOI: 10.1002/pon.3816
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances and related factors among family caregivers of patients with advanced cancer

Abstract: Sleep disturbances were common among the Taiwanese FCs of patients with advanced cancer. FCs with risk factors for sleep disturbances should be identified and provided assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 35 publications
6
47
0
2
Order By: Relevance
“…Most research on sleep disturbance in cancer caregivers has focused on early-stage disease. 27 However, the biological and psychological processes influencing sleep in cancer patients may be exacerbated in the context of advanced cancer. For example, advanced cancer patients often undergo more arduous treatments or have more pain than earlier-stage patients, both of which can impact sleep.…”
Section: Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Most research on sleep disturbance in cancer caregivers has focused on early-stage disease. 27 However, the biological and psychological processes influencing sleep in cancer patients may be exacerbated in the context of advanced cancer. For example, advanced cancer patients often undergo more arduous treatments or have more pain than earlier-stage patients, both of which can impact sleep.…”
Section: Current Studymentioning
confidence: 99%
“…Most research on sleep disturbance in cancer caregivers has focused on early‐stage disease . However, the biological and psychological processes influencing sleep in cancer patients may be exacerbated in the context of advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burton et al examined the hazards of caregiving and found that increased caregiving activity escalates the possibility of a fatigued caregiver, putting the caregiver at a higher risk of declining physical and mental health . Other studies have also observed that poor sleep and increased fatigue have negative effects on caregivers’ physical and mental health by exacerbating physical and psychological morbidity, and reducing quality of life . Although some studies have recognized the benefits of caregiving, most studies have reported a high prevalence of psychological distress, depression, and anxiety .…”
Section: Introductionmentioning
confidence: 99%
“…Identified risk factors for sleep problems include socio-demographics such as age 18,19 ; gender 18 ; race 20 ; marital status 21 ; education 22 ; and dependent family members. 23 Sleep problems have also been linked to lifestyle factors such as smoking 24 and physical activity 25 ; and health conditions such as obesity, 26 chronic diseases, 27 and musculoskeletal pain. 28 …”
Section: Introductionmentioning
confidence: 99%